1982
DOI: 10.1002/jmv.1890100305
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of antibodies to human cytomegalovirus in Urban, Kibbutz, and bedouin children in southern Israel

Abstract: Prevalence of antibody to human cytomegalovirus (CMV) was determined in a sample of 860 healthy children aged 1-13 years in Beer Sheva, in the Negev region of Israel. Three groups of children were tested: (1) urban Jewish children of low, middle, and high socioeconomic levels; (2) 8 rural communes (kibbutz) in which children live in close contact with each other from the 6th week of life under good hygienic conditions and a high standard of living; (3) Bedouin, seminomadic Arabs living in relatively poor hygie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

1984
1984
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 27 publications
1
6
1
Order By: Relevance
“…However, it is problematic to know how to ask about the frequency and/or intensity of kissing to explore this possible risk factor. In addition, the existing literature has documented that living in crowded situations (in a communal Kibbutz living situation) and group living has been associated with CMV infection [5,[35][36][37][38]; however, after studying specific group living situations individually and collectively as a variable, we found that it was not associated with CMV infection. While some studies have evaluated the number of individuals living in a home as a measure of "crowding" or "group living," we were concerned that adolescents answering a CASI may not know of the number of individuals living in the home earlier in life (from birth to the time of the questionnaire).…”
Section: Discussioncontrasting
confidence: 56%
“…However, it is problematic to know how to ask about the frequency and/or intensity of kissing to explore this possible risk factor. In addition, the existing literature has documented that living in crowded situations (in a communal Kibbutz living situation) and group living has been associated with CMV infection [5,[35][36][37][38]; however, after studying specific group living situations individually and collectively as a variable, we found that it was not associated with CMV infection. While some studies have evaluated the number of individuals living in a home as a measure of "crowding" or "group living," we were concerned that adolescents answering a CASI may not know of the number of individuals living in the home earlier in life (from birth to the time of the questionnaire).…”
Section: Discussioncontrasting
confidence: 56%
“…The report from the Center for Health Statistics demonstrates that receipt of child care is strongly associated with socioeconomic status. Women of low socioeco- (16,17). As illustrated in Table 3, high rates of CMV infection among children attending day care centers were later cormed in Sweden and have been reported in several studies in the United States (7,(18)(19)(20)(21)(22)(23)(24)(25)(26) those in day care than in those who stayed at home (20,21).…”
Section: Importance Of Day-care Centersmentioning
confidence: 85%
“…Previous studies have also noted that living in either group living or crowded situations have been positively associated with CMV infection [1] [33–36]. In our study, we examined group living exposure without a precise assessment of how much close contact that involved.…”
Section: Discussionmentioning
confidence: 99%